Potent inhibition of Western Equine Encephalitis virus by a fraction rich in flavonoids and phenolic acids obtained from Achyrocline satureioides - Sabini, Maria Carola (2016)
Achyrocline satureioides (Lam.) DC. Asteraceae, -marcela del campo-, possess several pharmacologicalproperties. Previously we reported antiviral activity of an aqueous extract of A. satureioides against analphavirus, Western Equine Encephalitis virus. Alphaviruses are highly virulent pathogens which causeencephalitis in humans and equines. There are no effective antiviral to treat its infections. The aim ofthis study was to evaluate in vitro cytotoxic and antiviral activities against Western Equine Encephalitisvirus of five water extract chromatographic fractions from A. satureioides and identify the main com-pounds of the bioactive fraction. Also, it was to assess in vivo cytogenotoxic ability of the active fraction.Cytotoxicity studies revealed low toxicity of the most of fractions in Vero and in equine peripheral bloodmononuclear cells. Antiviral studies showed that the water crude extract - Sephadex LH 20 - fraction 3MeOH-H2O (Fraction 3) was active against Western Equine Encephalitis virus with Effective Concentra-tion 50% = 5 g/ml. Selectivity Indices were 126.0 on Vero and 133.6 on peripheral blood mononuclearcells, four times higher than aqueous extract selectivity index. Regarding the mechanism of action wedemonstrated that F3 exerted its action in intracellular replication stages. Further, fraction 3 showedimportant virucidal action. Fraction 3 contains, in order of highest to lowest: chlorogenic acid, luteolin,5,7,8-trimethoxyflavone, 3-O-methylquercetin and caffeic acid. Fraction 3 did not induce in vivo toxicnor mutagenic effect. Therefore, it is safe its application as antiviral potential. Further studies of antiviralactivity in vivo will be developed using a murine model.